A computational method for the identification of new candidate carcinogenic and non-carcinogenic chemicals1. Issue 9 (11th September 2015) - Chen, Lei; Chu, Chen; Lu, Jing; Kong, Xiangyin; Huang, Tao; Cai, Yu-Dong
<x xml:space="preserve">Abstract</x> Several new candidate carcinogenic/non-carcinogenic chemicals obtained by our method exhibit structural dissimilarity with validated carcinogenic/non-carcinogenic chemicals.